2016
DOI: 10.3174/ajnr.a4650
|View full text |Cite
|
Sign up to set email alerts
|

Modified Core Biopsy Technique to Increase Diagnostic Yields for Well-Circumscribed Indeterminate Thyroid Nodules: A Retrospective Analysis

Abstract: BACKGROUND AND PURPOSE:The results of conventional core biopsy for some thyroid nodules with indeterminate cytology have still remained indeterminate. The aim of this study was to evaluate whether the ultrasonography-guided core needle biopsy technique containing the nodule, capsular portion, and surrounding parenchyma was more effective than a conventional method in enhancing diagnostic yield for circumscribed solid thyroid nodules without malignant sonographic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Considering NIFTP lacks malignant US features, US‐CNB could be applied to indeterminate thyroid nodules without the evidence of malignant features (i.e., K‐TIRADS categories 3 or 4). A modified CNB technique containing the nodule, capsular portion and surrounding parenchyma is helpful in reducing sampling error and archiving acceptable diagnostic clues of thyroid nodules . Therefore, a risk‐stratified approach requires US characteristics (US features, size of the primary tumour and tumour stability) and patient characteristics (age, comorbidities and compliance with follow‐up plans).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering NIFTP lacks malignant US features, US‐CNB could be applied to indeterminate thyroid nodules without the evidence of malignant features (i.e., K‐TIRADS categories 3 or 4). A modified CNB technique containing the nodule, capsular portion and surrounding parenchyma is helpful in reducing sampling error and archiving acceptable diagnostic clues of thyroid nodules . Therefore, a risk‐stratified approach requires US characteristics (US features, size of the primary tumour and tumour stability) and patient characteristics (age, comorbidities and compliance with follow‐up plans).…”
Section: Discussionmentioning
confidence: 99%
“…For non-NIFTP, however, there was no statistical difference in the surgical indication rates between the US-CNB and US-FNA groups. It should be recognized that US-CNB can lead to more surgery in patients with NIFTP, in comparison 37 Therefore, a risk-stratified approach requires US characteristics (US features, size of the primary tumour and tumour stability) and patient characteristics (age, comorbidities and compliance with follow-up plans). What is unique about our results is that malignant biopsy result (Bethesda and CNB diagnostic category VI) was equally most frequent in both US-FNA and US-CNB groups for non-NIFTP nodules.…”
Section: Discussionmentioning
confidence: 99%
“…CNB has been introduced as a complementary method for thyroid nodules because the large amount of specimen obtained can facilitate more detailed histologic evaluation and ancillary immunohistochemical staining (182324). Moreover, Nasrollah et al (46) have suggested a new sampling technique that includes the capsule of the nodule and the surrounding extranodular parenchyma, as well as nodular tissue (75). This technique could allow follicular neoplasm and unencapsulated non-neoplastic nodules to be distinguished by identifying the presence of a fibrous capsule on histologic evaluation.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…We obtained the second and third specimens according to the modified technique by Han et al 24 In addition, almost all the US-guided CNBs were performed by 2 experienced thyroid radiologists, and all biopsy specimens were reviewed by an expert pathologist. These are essential prerequisites for the successful diagnostic results.…”
Section: Discussionmentioning
confidence: 99%
“…The second and third biopsy specimens targeted the capsular portion (margin target) of the thyroid nodule to include a suspicious nodule, a capsule if present, and surrounding normal parenchyma (Fig 1). Previ-ously, Han et al 24 recommended the modified CNB technique, including both nodular tissue and the capsule of the nodule and/or extranodular thyroid tissue. We routinely performed USguided CNB for cytologically inconclusive nodules by using this protocol with 3 cores from June 2013.…”
Section: Ultrasonography and Ultrasonography-guided Core Needle Biopsmentioning
confidence: 99%